Serum biomarkers of treatment response within a randomized clinical trial for pulmonary tuberculosis. Issue 4 (July 2015) - Jayakumar, A.; Vittinghoff, E.; Segal, M.R.; MacKenzie, W.R.; Johnson, J.L.; Gitta, P.; Saukkonen, J.; Anderson, J.; Weiner, M.; Engle, M.; Yoon, C.; Kato-Maeda, M.; et al.
Summary Rationale Biomarkers for monitoring response to anti-tuberculosis treatment are needed. We explored immune markers previously published as having predictive capability for 8 week culture status in 39 adults enrolled in a clinical trial in Kampala, Uganda. Methods We consecutively selected 20 HIV-negative pulmonary TB subjects with positive cultures, and 19 subjects with negative cultures at the end of intensive phase therapy. At baseline and after 8 weeks, serum was assayed for nine cytokines and soluble cytokine receptors using multiplexed platforms or ELISA. We evaluated their association with week 8 culture status first using single-variable logistic models, then using cross-validated estimates of the C-statistic, a measure of discrimination, of candidate models including 2 or 3 analytes in addition to age. Results All but one analyte decreased from baseline to week 8 (all p < 0.01). Individual biomarkers were not associated with 8 week culture status. Logistic models including increasing age, higher baseline soluble tumor necrosis factor receptor alpha 1 (sTNF-R1), and higher week 8 C-reactive protein (CRP) concentration classified subjects by culture status with up to 85% accuracy and acceptable discrimination (cross-validated C-statistic 0.76) and calibration (Hosmer–Lemeshow P > 0.2). Conclusion Exploratory post-hoc models including sTNF-R1, CRP, and age, classified 8 week culture status with promising accuracy.